2021
DOI: 10.1021/acs.jpcc.0c10512
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Width Dependence of Lattice Thermal Conductivity in Ultranarrow Armchair Graphene Nanoribbons with Unpassivated Edges

Abstract: Low-dimensional materials attract extensive interest in electronic applications since the synthesis of graphene. Understanding the thermal transport in low-dimensional materials with shrinking characteristic size where strong confinement effect occurs is of importance for the thermal management of nanoelectronics. Recently, the atomically precise armchair graphene nanoribbons (AGNRs) with well-defined edges have been successfully synthesized. Serving as the fundamental functional elements, AGNRs can potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…156–158 However, in the ultrasmall size range, things may become different. Recently, Wang 159 et al investigated the width effect of ultranarrow armchair graphene nanoribbons, and showed that κ decreases with an increase in ribbon width, different from the width effect in larger scales. The explanation given by the authors is the changes in the lattice constants of different models and the phonon scattering channels of low frequency acoustic phonons.…”
Section: Intrinsic Structure Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…156–158 However, in the ultrasmall size range, things may become different. Recently, Wang 159 et al investigated the width effect of ultranarrow armchair graphene nanoribbons, and showed that κ decreases with an increase in ribbon width, different from the width effect in larger scales. The explanation given by the authors is the changes in the lattice constants of different models and the phonon scattering channels of low frequency acoustic phonons.…”
Section: Intrinsic Structure Engineeringmentioning
confidence: 99%
“…[156][157][158] However, in the ultrasmall size range, things may become different. Recently, Wang 159 et al investigated the width effect of ultranarrow armchair graphene nanoribbons, and showed that κ decreases with an increase in ribbon width, different from the width effect in larger scales.…”
Section: κðLþ ¼mentioning
confidence: 99%
“…Graphene nanoribbons (GNRs) have been extensively studied for their exciting properties and potential nanoscale applications [1][2][3][4][5] . Their extraordinary electronic and magnetic properties are strongly influenced by their structural boundaries and their widthes and edge geometry structures [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%